Association between strategies to prevent COVID-19 infection in long-term care facilities and mortality: the PIANO-COVID-19 study, a French multicentre cohort study - Sandrine Andrieu; Olivier Hanon; Galdric Orvoën; Olivier Guerin; Gaetan Gavazzi; Hubert Blain; Claire Roubaud-Baudron; Yves Rolland; Delphine Pennetier; Jason Shourick; Philipe de Souto Barreto; Céline Mathieu; et al. (BMJ Public Health)
Objective Evidence for the effectiveness of strategies that aimed to prevent COVID-19 infection on reducing mortality in long-term care facilities (LTCFs) is limited. Our aim was to investigate the association between strategies aimed at preventing COVID-19 infection and risk of death.Design The PIANO-COVID-19 study is a French national cohort study of LTCF residents. We compared strategies that aimed to prevent COVID-19 infection (eg, screening and isolation), characteristics of 107 LTCFs and their 8028 residents and mortality classified as all-cause deaths, COVID-19-related death and COVID-19-unrelated death. Short-term (within 1 month) and 1-year deaths after the first local COVID-19 peak were considered as the use of prevention strategies evolved during the course of the pandemic. Analyses were adjusted by age, gender, disability, comorbidity and occupancy of the local hospital.Results Among the 2202 (27.42%) 1-year all-cause deaths in 2020, 247 (11.21%) were related to COVID-19. The following preventative measures were related to a reduced risk of all-cause death: systematic mask wearing (HR 0.75 CI 95% (0.60–0.93)), screening of visitors for symptoms on entry (0.78 (0.62–0.97)), infection control training for staff (0.79 (0.63–0.98)) and systematic COVID-19 screening (with real-time PCR) of all staff and residents: staff (0.20 (0.05–0.84)) and residents (0.17 (0.04–0.76)). In contrast, difficulty in hospitalising (3.54 (1.53–8.17)) or a high occupancy rate of nearby hospitals (8.25 (2.19–31.01)) were associated with a higher risk of COVID-19-related deaths. At 1 month, screening of visitors for fever or symptoms on entry (0.04 (0–0.42)) and isolation of residents (no visiting) (0.05 (0.01–0.31)) were associated with a significant reduction in COVID-19 related death. None of the strategies that were investigated was associated with a higher risk of death.Conclusions We identified prevention strategies that appear to have been important in the limitation of COVID-19 related death in LTCFs and suggest widespread adoption may be beneficial in the case of a new epidemic.